Transcriptomic characterization of the functional and morphological development of the rumen wall in weaned lambs fed a diet containing yeast co-cultures of Saccharomyces cerevisiae and Kluyveromyces marxianus - Xu, Zixuan; Yang, Lan; Chen, Hui; Bai, Pengxiang; Li, Xiao; Liu, Dacheng (Frontiers in Veterinary Science, 2025)
IntroductionIn lambs, the function of the rumen is incompletely developed at weaning, and the inclusion of yeast cultures in the diet can profoundly influence the morphological and functional development of the rumen.MethodsIn this study, the effects of Saccharomyces cerevisiae and Kluyveromyces marxianus (NM) yeast co-cultures on ruminal histomorphology were assessed, and corresponding transcriptomic changes within the rumen epithelium were identified. In total, 24 lambs were grouped into four groups of six lambs including a control (C) group fed a basal diet, and N, M, and NM groups in which lambs were fed the basal diet, respectively, supplemented with Saccharomyces cerevisiae yeast cultures (30 g/d per head), Kluyveromyces marxianus yeast cultures (30 g/d per head), and co-cultures of both yeasts (30 g/d per head), the experiment lasted for 42 d.ResultsIn morphological analyses, lambs from the NM group presented with significant increases in papilla length, papilla width, and epithelial thickness in the rumen relative to lambs in the C group (p < 0.05). Transcriptomic analyses revealed 202 genes that were differentially expressed between samples from the C and NM groups, with the largest proportion of these genes being associated with the oxidative phosphorylation pathway. In a weighted gene coexpression network analysis, a positive correlation was observed between the MEgreen and MEpurple modules and rumen morphology. Of these modules, the MEgreen module was found to be more closely linked to fatty acid metabolism and oxidative phosphorylation, whereas the MEpurple module was linked to oxidative phosphorylation and fatty acid degradation. Ultimately, these results suggest that dietary supplementation with NM has driven the degradation of fatty acids, the induction of oxidative phosphorylation, the acceleration of lipid metabolism, the production of ATP to sustain ruminal growth, and the maintenance of intracellular NADH/NAD+ homeostasis on weaned lambs and is superior to single yeast fermentation.DiscussionThese results thus offer a theoretical foundation for further studies examining the mechanisms through which NM cultures can influence ruminal development in lambs.